STUDIES OF THE ENDEMICITY OF PATHOGENIC TRYPANOSOMES: AN IMPLICATION FOR HUMAN TRYPANOSOMIASIS CONTROL IN GWAGWALADA TOWN, FCT-ABUJA. - U.N, GIMBA, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
A total of 636 complrising of cattle, goats and sheep was investigated for the presence of Trypanosomes infection in Gwagwalada slaughter house, between the month of (July 2015 to November 2015) and the prevalence rates in cattle, goats and sheep were found to be 6.60%, 5.70% and 4.72% respectively. Wet, thin, thick films, animal inoculation, haematocrit centrifugation technique and buffy coat methods were used to detect trypanosomes in the blood of the animals. The packed cell volume (PCV) was also determined. Mean PCV of infected cattle was 6.60% against uninfected cattle 93.40%. In goats, the PCV was 5.70%, uninfected goats 94.30%; while that of sheep was 4.72% and uninfected 95.30%. Trypanosoma vivax infection accounted for 60%, T. brucei 26.7% and T. congolense 13.38% in cattle. In goats, T. vivax infection accounted for 50%, T. brucei 41.7% and T. congolense 8.3%. Also T. vivax infection accounted for 64%, T. brucei 26% and T. congolense 0% in sheep. Sex did not significantly (P>0.05) affect infection rates. Although the prevalence rate of trypanosomiasis in cattle, goats and sheep appeared to be reducing compared to the previous works, trypanosomiasis remains an economically important in susceptible animals despite the reduction in prevalence rates in Nigeria.